Deliverable D 7.7 A model Business Continuity and Resilience Plan and Disaster Management Plan Framework - Mariantonietta Morga; Keith Jones; Nadeeshani Wanigarathna; Femke Mulder; Federica Pascale; Alberto Vezzoso; Chen Huang; Håkan Bolin; Nicos Melis; Dragos Toma-Danila (Zenodo, 2022)
A large part of Europe is at risk from earthquakes. To address this, the TURNkey research project aimed to foster urban resilience to earthquakes in Europe. The project covered 1) Operational Earthquake Forecasting (OEF) and simulations for seismic risk assessments during the period before an earthquake event; 2) Earthquake Early Warning (EEW) for near real-time seismic information during an earthquake event; and coordination and information management to support a Rapid Response to Earthquakes (RRE). TURNkey has worked towards the development of a Forecasting, early Warning, Consequence prediction and Response (FWCR) platform, which effectively integrates OEF, EEW and RRE. The project’s goal was to close the gap between theoretical systems and their practical application in Europe. To this end, TURNkey researchers have worked with potential end-users to co-design an FWCR platform for strategic and operational decision making in the face of seismic risk and earthquake-related disasters. The approach used is called Participatory Action Research (PAR). With PAR, potential end-users take an active part in the research process as do those responsible for product/project design and development (i.e., the TURNkey scientists and engineers). The end-users included in PAR for TURNkey were civil protection, first responders, business organisations and critical infrastructure providers. TURNkey worked with potential end-users in its 6 geographical testbeds: Romania (TB-1); France (TB-2); Iceland (TB-3); Greece (TB-4); Italy (TB-5) and the Netherlands (TB-6). The TURNkey concept model was developed over three PAR cycles. This report describes the process and findings of the 3nd and final PAR cycle in the TURNkey project. It is divided into 4 sections: the development of a business continuity and disaster management framework that can be used to integrate the TURNkey FWCR Platform into earthquake business continuity and disaster management plans; the development of a model business continuity for business or critical ...